E-voting, Information Gap, and The Digital Divide in Zimbabwe - Tom, Teckshawer (Technium Social Sciences Journal, 2023)
The objective of this research was to establish if Zimbabwe has the potential and Information Communication Technology (ICT) capacity to implement e-voting methods in the country's often discredited electoral process. The study adopted qualitative methods and secondary data collected from relevant reports, questionnaires randomly distributed to the general populace as well as interviews with Zimbabwe Electoral Commission (ZEC) and the Postal and Telecommunications Regulatory Authority of Zimbabwe (POTRAZ) officials. The paper highlights the global and national status of ICT adoption in Zimbabwe which is the key driver to the successful implementation of e-voting, internet coverage, and use in the country. The research also investigated how Zimbabwe citizens in the diaspora, through new Internet platforms, can exercise their right to participate in the country's political discourse and vote using the e-voting model. The findings indicate that though it can be done, it is not being practiced. Hence citizens in the diaspora are being excluded from the electoral process. The research findings also give credence suggesting Zimbabwe has sufficient infrastructure to implement e-voting methods as a trial in selected local government elections.